Immersive Virtual Reality Games for Rehabilitation of Phantom Limb Pain - Güngör, Feray; Tarakçı, Ela; Çubuk, Abdurrahman; Aydın, Muhammed Ali; AKBULUT, AKHAN (My University, 2019)
Serious games mostly associated with rehabilitation systems with state-of-the-art virtual reality hardware and software products. This approach benefits from gamification that improves the participant’s engagement and makes cybertherapy sessions fun and interactive. This paper describes four different serious games for the rehabilitation of phantom limb pain (PLP) syndrome. Each immersive virtual reality game is designed to overcome the negative effects of PLP for different amputation regions including below-elbow, above-elbow, below-knee and above knee. We aimed to propose a low-cost, effective rehabilitation system that can be used at home instead of hospital-oriented physiotherapy routine. We used the Kinect sensor, a wearable surface electromyography (sEMG) sensor, and the Oculus Rift virtual reality headset to provide a longer therapeutic interaction between the patient and the cyber-therapy environment. Alpha test results of a pilot study with unimpaired healthy participants reveal the proposed system works practically in the home environment.
Keywords: Cyber Therapy; Gamification; Phantom Limb Pain; Serious Games; Virtual Reality